2016
DOI: 10.4103/0253-7613.190757
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between three option, four option and five option multiple choice question tests for quality parameters: A randomized study

Abstract: Background:Most of the academic teachers use four or five options per item of multiple choice question (MCQ) test as formative and summative assessment. Optimal number of options in MCQ item is a matter of considerable debate among academic teachers of various educational fields. There is a scarcity of the published literature regarding the optimum number of option in each item of MCQ in the field of medical education.Objectives:To compare three options, four options, and five options MCQs test for the quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 14 publications
(34 reference statements)
3
13
1
Order By: Relevance
“…We conclude, therefore, that items containing 3-options are equally effective as items with 4-options with respect to both item difficulty and item discrimination. Our findings are in general agreement with previous studies evaluating the performance of medical [ 15 , 16 , 17 ] and nursing students [ 18 , 19 ] given MCQs with three to five options. These studies showed no statistically significant differences in item discrimination, item difficulty, or the mean examination scores when MCQs were administered with three versus four option answer choices [ 15 , 16 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…We conclude, therefore, that items containing 3-options are equally effective as items with 4-options with respect to both item difficulty and item discrimination. Our findings are in general agreement with previous studies evaluating the performance of medical [ 15 , 16 , 17 ] and nursing students [ 18 , 19 ] given MCQs with three to five options. These studies showed no statistically significant differences in item discrimination, item difficulty, or the mean examination scores when MCQs were administered with three versus four option answer choices [ 15 , 16 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…While some may argue that the inclusion of more options in an MCQ reduces the 'guessing effect' , others have demonstrated that additional options beyond three do not make much difference; in fact, reducing the list of available responses to three options can actually improve psychometric features. 22,23 Furthermore, it is easier to develop three rather than four or five MCQ options and more effective to have fewer options with a greater number of functional distractors in comparison to increased options and more NFDs. Tarrent et al suggested including three instead of four options, as such questions require less time to be constructed and the performance for both is equal.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the number of options, there is evidence that suggests the superiority of four-option MCQs relative to the fiveoption type (Fozzard et al 2018). Moreover, studies highlighted the advantages of three-option MCQs over the four-option type (Vegada et al 2016;Rahma et al 2017).…”
Section: Discussionmentioning
confidence: 99%